PENGGUNAAN ANALISIS KETAHANAN HIDUP UNTUK PENENTUAN PERIODE GARANSI DAN HARGA PRODUK PADA DATA WAKTU HIDUP LAMPU NEON - Dian Ika Pratiwi; Triastuti Wuryandari; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Tubular lamp industries nowadays are highly competitive in order to create the most-demanded products. The main factor of consumer’s preferences in this product is quality, particularlythe durability as well as the price. Firstly, the longer a tubular/fluorescent lamp works - which indicates the quality of the fluorescent light - the better. The durability can be also a guideline for the company to determine the warranty cost by finding a value of Mean Time to Failure (MTTF). The next factor for consumers to buy or not to buy the lamp is the price of it. The price of a product can be obtained by calculating its production cost, invariably the warranty cost. In the case of tubular lamp, we use Free Replacement Warranty (FRW) policy and found that the warranty time given by the company for 365 days is precisely compared with the value of MTTF of 391 days. Meanwhile the warranty cost which is calculated by using FRW policy isRp 4.108,00. Keywords: tubular lamp, Mean Time to Failure (MTTF), warranty, cost, Free Replacement Warranty (FRW).